Where were the doctors when the Roman Empire died? - Francois P. Retief; Louise Cilliers (Acta Theologica)
The notion that inadequate health services might have been one of the reasons for the fall of the Roman Empire is investigated. Despite many factors preventing the early development of an adequate public health service, the Romans had achieved much by the 5th century AD. Apart from many laws promoting public health, various official measures were taken by the Roman government, for example the appointment of state physicians and free medical services for the poor. But the greatest contribution of the Romans was the provision of facilities which served as an indispensable infrastructure for public health care, such as the provision of an ample supply of pure water, public baths, advanced measures for the disposal of sewage, and somewhat later under the influence of Christianity, hospitals for the general public. Although there were still deficiencies, the Roman government cannot be criticised for laxity as far as the provision of health services was concerned. Inasmuch as they were in default, it was because of lack of scientific medical knowledge which only evolved c. 1 500 years later.